Comparative activities of LY 333328, a new glycopeptide, against penicillin-susceptible and -resistant pneumococci. - Fasola, E (1996)
Microdilution MIC testing was used to test the susceptibility of 202 pneumococci to LY 333328 and six other agents. LY 333328 was the most active glycopeptide (MIC at which 90% of the pneumococci were inhibited [MIC90], 0.008 microgram/ml), followed by teicoplanin (MIC90, 0.06 microgram/ml) and vancomycin (MIC90, 0.5 microgram/ml). Rifampin resistance was seen in some penicillin-resistant strains. The MICs of imipenem and ceftriaxone rose with those of penicillin. Time-kill testing confirmed the excellent antipneumococcal activity of LY 333328.